Object oriented program development using java - Bronson, Gary J.
Newly updated for JDK 5.0, best-selling author Gary J. Bronson's text provides students with a solid but gentle introduction to object-oriented Java programming in the first chapter. Objects and classes are defined in the context of a practical recipe analogy, ensuring that students will be able to grasp these challenging topics. Students will emerge from this text with the ability to code basic CS1 Java programming problems within a class-centered environment